2019
DOI: 10.1248/bpb.b19-00073
|View full text |Cite
|
Sign up to set email alerts
|

Role of Aquaporin-3 in Intestinal Injury Induced by Sepsis

Abstract: Aquaporin-3 (AQP3) is expressed in various parts of the intestine, where it regulates the proliferation and migration of intestinal epithelial cells and the transport of glycerol and hydrogen peroxide. Our study aimed to investigate the effect on the expression of AQP3 of intestinal injury in septic mice and whether oral administration of glycerol can reduce intestinal epithelial injury and barrier disorder by acting as a partial substitute for the function of AQP3. We established a sepsis model by cecal ligat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…At the same time, the results of an intestinal mucosal injury model induced by sepsis showed that AQP3 expression was downregulated in response to the intestinal injury and inflammation caused by the sepsis. Glycerol supplementation can partially improve small‐bowel pathological damage, including reducing intestinal epithelial cell permeability and reducing small intestinal mucosal damage (Zhu et al, 2019). These all reveal the protective effect of AQPs on the intestinal barrier, and the mechanism may be that AQPs can regulate the concentration of glycerol and ATP biosynthesis, thereby affecting cell proliferation.…”
Section: Aquaporins and Intestinal Healthmentioning
confidence: 99%
“…At the same time, the results of an intestinal mucosal injury model induced by sepsis showed that AQP3 expression was downregulated in response to the intestinal injury and inflammation caused by the sepsis. Glycerol supplementation can partially improve small‐bowel pathological damage, including reducing intestinal epithelial cell permeability and reducing small intestinal mucosal damage (Zhu et al, 2019). These all reveal the protective effect of AQPs on the intestinal barrier, and the mechanism may be that AQPs can regulate the concentration of glycerol and ATP biosynthesis, thereby affecting cell proliferation.…”
Section: Aquaporins and Intestinal Healthmentioning
confidence: 99%
“…Thus, ameliorating the immunosuppression state may be beneficial to the treatment of clinical sepsis. intestinal injury is one of the main pathological characteristics of sepsis, which significantly influences the health of patients with sepsis (26). in the present study, a sepsis model was established by clP in rats to simulate the pathological state of sepsis-induced intestinal barrier injury.…”
Section: Discussionmentioning
confidence: 97%
“…It is also known that AQPs in the gastrointestinal tract take part in processes connected with the secretion of saliva, gastric juice and intestinal hormones and enzymes (Delporte, 2017;Matsuzaki et al, 2017). Previous studies also found that AQPs are involved in the support of normal functions of the intestinal barrier (Zhang et al, 2011), as well as take part in pathological processes during diseases of the digestive system and mechanisms connected with diarrhoea (Kon et al, 2018;Xiang et al, 2018;Wang et al, 2019), as well as in physiological processes, including the growth and maturation of the GI tract, as well its adaptation to changes in the diet. Table 1 Distribution of AQPs in the innervation of digestive systema summary of current knowledge HUMAN AQP1 in intraganglionic glial cells in the oesophagus and glial cells within neuronal plexuses in the pancreas.…”
Section: Possible Functions Of Aqps In the Nervous Structures Supplyimentioning
confidence: 99%
“…Apart from participation in the transport of water and other substances, AQPs are involved in many regulatory processes, such as the proliferation and migration of cells, phagocytosis, tissue regeneration, apoptosis and many others (Szpilbarg et al, 2016;Pelagalli et al, 2018;Yasumitsu et al, 2018;Guo et al, 2019). Because the digestive system is the place where water transport is very intensive, high levels of almost all isoforms of aquaporins (AQP1-AQP11) have been found in the gastrointestinal (GI) tract and other digestive organs, such as salivary glands, pancreas, liver, gallbladder and bile duct (Zhu et al, 2016(Zhu et al, , 2019Zhang et al, 2019). Primarily, AQPs in the digestive system have been found in the epithelial cells, glands and microvessels (Zhu et al, 2016;Zhu et al, 2017, Zhang et al, 2019.…”
mentioning
confidence: 99%